Efeitos comportamentais e moleculares de fitocanabinoides em camundongos submetidos ao modelo da sensibilização locomotora induzida pelo etanol - Filev, Renato [UNIFESP] (2015)
Drug dependence, including alcoholism, is a neuroadaptative process induced by mesolimbic dopaminergic pathway sensitization. Several neurochemical mechanisms increase the incentive salience of motivational agents, in our case, ethanol. This sensitization seems to play an important role on craving development, and when associated to cues or stress, could induce relapse. Experimental studies suggest that endocannabinoid system is involved on ethanol pharmacological effects and in the modulation of motivational circuit. Recently, we have found that rodents submitted to locomotor sensitization and then to 5 days of drug withdrawal show increased type 1 cannabinoid receptor (CB1) expression on prefrontal cortex and striatum. Furthermore, case reports and observational studies suggest Cannabis use to mitigate the problematic use of ethanol. Therefore,here we aimed to verify whether phytocannabinoids (CBD and THC) influence the maintenance of locomotor sensitization induced by ethanol. Additionally, we investigated CB1 receptor and c-Fos expression. CBD (2.5; 5.0; 10 and 50 mg/kg, i.p.) did not affect the maintenance of locomotor sensitization. On the other hand, there was a significant inhibitory effect of THC (2.5 mg/kg, i.p.) in this behavioral response, when administered alone or in conjunction with CBD (in a 1:1 proportion). THC did not change consistently c-Fos expression, but prevented CB1 receptor upregulation in the ventral striatum. Contrary to our hypothesis, there was no correlation between behavioral and molecular results. The behavioral results point to potential therapeutic effects of THC in alcoholism. THC/CBD association showed to be effective on the proposed model. Thus, as already recognized for the treatment of other human conditions, our findings bring new insights for the development of clinical trials using the association of THC/CBD in alcohol-related problems.